A surge in female condom distribution during the COVID-19 pandemic in Gauteng province, South Africa - Cyril Bernsah Fonka; Nicola Christofides (Contraception and Reproductive Medicine)
Abstract Background Female Condoms are 90–95% effective against HIV transmission when correctly and consistently used and are also cost-effective. In general, condoms prevent sexually transmitted infections (STIs) and unwanted pregnancies. Although the COVID-19 pandemic had the potential to undermine routine healthcare services delivery and utilisation, there is limited evidence about the pandemic’s effect on Female Condom uptake in Gauteng, one of the hardest-hit provinces in South Africa. This study aimed to compare female condom distribution in Gauteng Province, South Africa, before and during COVID-19, to inform decision-making for the attainment of universal access to sexual and reproductive health (SRH) by 2023 as per the sustainable development goal 3.7 and also, to empower women over their SRH during future pandemics. Methods This secondary data anslysis examined the percentage change in routine female condom distribution in Gauteng province and its five districts as an indirect effect (lockdown) of the COVID-19 pandemic, by comparing the aggregated District Health Information System (DHIS) data collated from primary health care facilities within the ditrict, before COVID-19 (2018–2019) and during COVID-19 (2020). Analysis in MS Excel 2016 illustrates the changes in the patterns and the trend in female condom distribution over the study period. Results In 2020, during the COVID-19 pandemic, Gauteng province experienced a 43.7% increase in female condom distribution compared to the pre-COVID-19 period of 2019. The highest female condom distribution during the pandemic was observed in the Ekurhuleni Metropolitan (150.0%), followed by the Sedibeng (92.8%) and the Johannesburg Metropolitan (67.9%) districts respectively. However, the Tshwane Metropolitan (-8.5%) and the West Rand (-16.6%) districts experienced a decline in female condom distribution during COVID-19. Conclusion Gauteng province witnessed a substantial surge in female condom distribution during COVID-19 in 2020, with a disproportionate district variation in demand. Female condom distribution is crucial, necessitating its enhancement and the continuum of distribution and stakeholders stockpiling at all times with particular attention to a potential increase in demand during outbreaks with lockdowns. Undisrupted access to female condoms will enable a consistent and correct use and empower women against HIV, STIs and unintended pregnancies, as a strive towards universal access to SRH.